Policing the University: A Global Trend - Eve Darian-Smith (Revista de Direito Econômico e Socioambiental)
The essay examines the increasing policing of universities and colleges and specifically the diminishing of faculty and students’ right to peacefully assemble and challenge oppressive governance. I argue that we must understand the escalating presence of riot police on university grounds as part of a wider trend to prevent all forms of public protest. Thinking about policing students and scholars as constituting part of a global anti-protest trend is essential for several reasons. First, it avoids getting bogged down in detailed legal and constitutional debates about what constitutes academic freedom and what activities justify police intervention that may vary within and across national contexts. This helps overcome the state-centered approach that continues to dominate analyses of higher education and opens up new comparative and transnational perspectives and questions. Secondly, and more importantly, without considering the global context in which localized attacks on universities occur we will not fully comprehend why policing is escalating, nor develop strategies to resist far-right regimes that suppress scholars and wider societies’ ability to challenge rising authoritarianism.